Randomized controlled trial of mailed Nicotine Replacement Therapy to Canadian smokers: study protocol - Leatherdale Scott T; Cunningham John A; Selby Peter L; Tyndale Rachel F; Zawertailo Laurie; Kushnir Vladyslav (BMC, 2011)
Abstract Background Considerable public health efforts are ongoing Canada-wide to reduce the prevalence of smoking in the general population. From 1985 to 2005, smoking rates among adults decreased from 35% to 19%, however, since that time, the prevalence has plateaued at around 18-19%. To continue to reduce the number of smokers at the population level, one option has been to translate interventions that have demonstrated clinical efficacy into population level initiatives. Nicotine Replacement Therapy (NRT) has a considerable clinical research base demonstrating its efficacy and safety and thus public health initiatives in Canada and other countries are distributing NRT widely through the mail. However, one important question remains unanswered - do smoking cessation programs that involve mailed distribution of free NRT work? To answer this question, a randomized controlled trial is required. Methods/Design A single blinded, panel survey design with random assignment to an experimental and a control condition will be used in this study. A two-stage recruitment process will be employed, in the context of a general population survey with two follow-ups (8 weeks and 6 months). Random digit dialing of Canadian home telephone numbers will identify households with adult smokers (aged 18+ years) who are willing to take part in a smoking study that involves three interviews, with saliva collection for 3-HC/cotinine ratio measurement at baseline and saliva cotinine verification at 8-week and 6-month follow-ups (N = 3,000). Eligible subjects interested in free NRT will be determined at baseline (N = 1,000) and subsequently randomized into experimental and control conditions to receive versus not receive nicotine patches. The primary hypothesis is that subjects who receive nicotine patches will display significantly higher quit rates (as assessed by 30 day point prevalence of abstinence from tobacco) at 6-month follow-up as compared to subjects who do not receive nicotine patches at baseline. Discussion The findings from the proposed trial are timely and highly relevant as mailed distribution of NRT require considerable resources and there are limited public health dollars available to combat this substantial health concern. In addition, findings from this randomized controlled trial will inform the development of models to engage smokers to quit, incorporating proactive recruitment and the offer of evidence based treatment. Trial Registration ClinicalTrials.gov: NCT01429129